Omalizumab in Food Allergy in Children: Current Evidence and Future Perspectives - Cristiana Indolfi; Alessandra Perrotta; Giulio Dinardo; Angela Klain; Carolina Grella; Paola Palumbo; Michele Miraglia del Giudice (Life)
Omalizumab (OMA) is gaining recognition as a promising therapeutic approach for IgE-mediated food allergies in pediatric patients. We conducted a review analyzing 22 studies, including randomized controlled trials, observational studies, and case reports, to evaluate the efficacy and safety of OMA in food allergy management in children and adolescents. The results indicate that OMA, whether used as monotherapy or in combination with oral immunotherapy (OIT), significantly increases allergen tolerance, reduces the severity of allergic reactions, and improves patients’ quality of life. When used alongside OIT, OMA reduced adverse reactions during dose escalation and maintenance phases, facilitating safer and more effective desensitization. Additionally, OMA demonstrated benefits beyond food allergy management, including improved asthma control and a reduction in food allergy-related anxiety. However, challenges remain, including high costs, the need for standardized treatment protocols, and limitations related to total IgE thresholds for eligibility. While OMA has been FDA-approved for food allergy treatment in the United States, further research is needed to establish long-term efficacy, optimal dosing strategies, and its role in sustained tolerance development. Future research should focus on optimizing treatment protocols and identifying which patients will benefit the most. Integrating omalizumab into food allergy management could revolutionize pediatric care, offering hope for a safer, more effective approach to desensitization.